A search for cosmogenic neutrinos with the ARIANNA test bed using 4.5 years of data - Anker, A.; Barwick, S. W.; Klein, S. R.; Kleinfelder, S. A.; Lahmann, R.; Latif, U.; Nam, J.; Novikov, A.; Nelles, A.; Paul, M. P.; Persichilli, C.; Plaisier, I.; et al. (2019)
The primary mission of the ARIANNA ultra-high energy neutrino telescope is to uncover astrophysical sources of neutrinos with energies greater than $10^{16}eV$. A pilot array, consisting of seven ARIANNA stations located on the surface of the Ross Ice Shelf in Antarctica, was commissioned in November 2014. We report on the search for astrophysical neutrinos using data collected between November 2014 and February 2019. A straight-forward template matching analysis yielded no neutrino candidates, with a signal efficiency of 79%. We find a 90% confidence upper limit on the diffuse neutrino flux of $E^2Φ=1.7× 10^{-6}\mathrm{GeV cm^{-2}s^{-1}sr^{-1}}$ for a decade wide logarithmic bin centered at a neutrino energy of $10^{18}eV$, which is an order of magnitude improvement compared to the previous limit reported by the ARIANNA collaboration. The ARIANNA stations, including purpose built cosmic-ray stations at the Moore's Bay site and demonstrator stations at the South Pole, have operated reliably. Sustained operation at two distinct sites confirms that the flexible and adaptable architecture can be deployed in any deep ice, radio quiet environment. We show that the scientific capabilities, technical innovations, and logistical requirements of ARIANNA are sufficiently well understood to serve as the basis for large area radio-based neutrino telescope with a wide field-of-view.